2011
DOI: 10.1016/j.vetmic.2011.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Trial design to estimate the effect of vaccination on tuberculosis incidence in badgers

Abstract: The principal wildlife reservoir of Mycobacterium bovis in Ireland is the European badger. Studies in the Republic of Ireland (RoI) have shown that badgers culled in association with cattle herd tuberculosis (TB) breakdowns (focal culling) have a higher prevalence of infection than the badger population at large. This observation is one rationale for the medium term national strategy of focal badger culling. A vaccination strategy for the control of TB in badgers is a preferred long-term option. The Bacillus C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 22 publications
(23 reference statements)
0
47
0
Order By: Relevance
“…Issues relating to licensing (Murphy et al, 2008) and delivery have also been considered. A field trial was subsequently conducted over three zones covering approximately 755 km 2 in Co. Kilkenny Aznar et al, 2011), and analyses are now underway, focusing on incidence (Aznar et al, 2013;Aznar et al, 2014) and prevalence data. A non-inferiority trial, comparing badger vaccination and culling, is currently being conducted in 6 counties in Ireland (J. O'Keeffe, pers.…”
Section: The Importance Of Wildlife In Btb Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Issues relating to licensing (Murphy et al, 2008) and delivery have also been considered. A field trial was subsequently conducted over three zones covering approximately 755 km 2 in Co. Kilkenny Aznar et al, 2011), and analyses are now underway, focusing on incidence (Aznar et al, 2013;Aznar et al, 2014) and prevalence data. A non-inferiority trial, comparing badger vaccination and culling, is currently being conducted in 6 counties in Ireland (J. O'Keeffe, pers.…”
Section: The Importance Of Wildlife In Btb Persistencementioning
confidence: 99%
“…Progress with the former will lead to a further drop in herd bTB incidence in Ireland, but not to the point of eradication. Critical information about the latter will become available shortly, based on results from the Kilkenny badger vaccination field trial (Sheridan, 2011;Aznar et al, 2011Aznar et al, , 2013Aznar et al, , 2014. A noninferiority trial is currently being conducted in six counties in Ireland evaluating the relative impacts of badger culling and vaccination on herd-level bTB prevalence (J. O'Keeffe, pers.…”
Section: Evaluating National Progressmentioning
confidence: 99%
“…Modelling had suggested that it would not be necessary for the vaccine to provide full protection to the badger to have significant effect on the overall programme. (Aznar et al, 2010) The question then was one of feasibility. A study was undertaken in 1994, consulting with experts worldwide, and this concluded that the strategy was feasible (Report of Steering Committee, 1994).…”
Section: Wildlife Disease Control Strategy Vaccination Development Prmentioning
confidence: 99%
“…A series of pen-based vaccination trials have been conducted, where badgers were vaccinated with Bacillus Calmette-Guerin (BCG) and subsequently challenged with M. bovis , and the impact of vaccination on pathology, bacteriology and progression of infection in badgers has previously been reported [6][9]. Subsequent to this work, a field trial commenced in county Kilkenny, in 2009, to determine the effects of badger vaccination on M. bovis transmission in badgers under field conditions [10]. The field trial design will enable comparison of bTB incidence between vaccinated and unvaccinated badgers in three areas of differing vaccine coverage (100, 50 and 0%).…”
Section: Introductionmentioning
confidence: 99%
“…There is now a better understanding of options to address the first and third of these challenges [10], [11]. In this paper, we consider the second of these challenges, that is, the need for a test to identify the infection status of individual badgers at each capture event.…”
Section: Introductionmentioning
confidence: 99%